2009
DOI: 10.1080/17429140802527169
|View full text |Cite
|
Sign up to set email alerts
|

Infection induced oxidative cross-linking of hydroxyproline-rich glycoproteins (HRGPs) is associated with restriction ofColletotrichum sublineolumin sorghum

Abstract: Hydroxyproline-rich glycoproteins (HRGPs) accumulation and oxidative cross-linking is one of the earliest defense responses in plants against pathogen infection. In the present study HRGP accumulation in three sorghum genotypes i.e. SC146 (resistant), SC326 (intermediately resistant) and BTx623 (susceptible) as a response to Colletotrichum sublineolum isolate CP2126 infection is elucidated. HRGPs were monitored by hydroxyproline (Hyp) estimation. In genotypes SC146 and SC326 there was a significantly higher am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…HRGPs play a leading role in plant defense, e.g., HRGPs were induced in incompatible plant-pathogen interactions [18,89] and rapidly deposited in the cell wall after pathogen infection [90,91]. Such a defense ability is a result of the intra-and inter-molecular cross-linking in plant cell walls after HRGPs become insolubilized [88,92]. In this process, the interaction between insoluble HRGPs and the polysaccharide reduces the hydration and pectin mobility of the cell wall thus leading to the increase of rigidity and resistance of cell wall against pathogen invasion [92].…”
Section: Physical Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…HRGPs play a leading role in plant defense, e.g., HRGPs were induced in incompatible plant-pathogen interactions [18,89] and rapidly deposited in the cell wall after pathogen infection [90,91]. Such a defense ability is a result of the intra-and inter-molecular cross-linking in plant cell walls after HRGPs become insolubilized [88,92]. In this process, the interaction between insoluble HRGPs and the polysaccharide reduces the hydration and pectin mobility of the cell wall thus leading to the increase of rigidity and resistance of cell wall against pathogen invasion [92].…”
Section: Physical Barriermentioning
confidence: 99%
“…Such a defense ability is a result of the intra-and inter-molecular cross-linking in plant cell walls after HRGPs become insolubilized [88,92]. In this process, the interaction between insoluble HRGPs and the polysaccharide reduces the hydration and pectin mobility of the cell wall thus leading to the increase of rigidity and resistance of cell wall against pathogen invasion [92]. Furthermore, it was found that intra-and inter-molecular cross-linking took place in glycosylated HRGPs under the catalysis of the peroxidase.…”
Section: Physical Barriermentioning
confidence: 99%
“…According to several authors [6971], extensins undergo peroxidase-mediated oxidative cross link during pathogen infection thus decreasing the permeability of the cell wall. Similar effect was also proposed for at least some AGPs classes [72].…”
Section: Proteins Of the Cell Wallmentioning
confidence: 99%
“…HRGP contents were assessed according to the method of Basavaraju et al (2009) and Shailasree et al (2004) with slight modifications. To prepare the cell wall, the orange rinds (1 g) were homogenized using a pestle and mortar at 4 C in 100 mM phosphate buffer at pH 7.2.…”
Section: Measurements Of Pectin Hydroxyproline-rich Glycoproteins (Hmentioning
confidence: 99%